ANALYSIS OF FINANCIAL DIGITALIZATION ON BUMDES AS A KNOWLEDGE-BASED VIEW PERSPECTIVE: (Case of Bumdes Bumirejo, Dampit, Malang Regency) - Kustiningsih, Nanik (Dinasti International Journal of Digital Business Management, 2022)
Research on knowledge management is centered on the question of how companies from small to large scale manage their assets, so that they can produce a comparative advantage. The times have forced economic actors to adapt in order to answer any existing challenges. The use of appropriate technology is a central issue in responding to the challenges that arise. Large companies have sufficient human resources to integrate technology with existing governance. However, this is not necessarily the case with small economic units such as Village Owned Enterprises (BUMDes). This study aims to explain how BUMDes manages the new knowledge gained, thereby contributing to increased performance (knowledge-based strategy). The method used is a qualitative research method with an exploratory approach. The process of data collection and analysis is divided into two stages. First, in-depth interviews with several predetermined samples. The results of the interviews were then analyzed to obtain preliminary results or the level of knowledge currently owned by BUMDes. The second stage is training and workshops for partners to introduce new types of knowledge, namely digital-based financial management. Furthermore, data collection was carried out through focus group discussions (FGD). The results of this study are the performance of BUMDes Bumirejo is increasing and contributing to the village economy, especially in the transparency of digital-based financial management. The main key. To achieve the desired hope is to improve the village economy. Trust, commitment and sustainability of BUMDes development.